Reverse Engineering Design Of Ceiling Lamp Changer To Increase Product Value By Using Dfma Methode - Bayu Pranoto; Eva Weddakarti; Rilis Eka Perkasa; Silvia Rahmi Ekasari; Nicky Suwandhy Widhi Supriyanto (CV. Syntax Corporation Indonesia, 2025)
The prevalent manual method of replacing ceiling lamps, which often involves climbing on unstable furniture, poses significant safety risks, including potential falls, electrocution, and other severe injuries. This common practice underscores an urgent need for safer and more efficient lamp maintenance solutions in both domestic and commercial settings. This research aims to mitigate these inherent dangers by developing and upgrading conventional ceiling lamp changers into a semi-automatic system. The primary objectives are to enhance the safety, speed, and overall ease of the lamp replacement process, thereby effectively minimizing the risk of user injury. The proposed methodology involves designing a semi-automatic ceiling lamp changer by integrating a control switch mechanism that enables remote rotation of the lamp holder. This innovative approach will facilitate the safe removal and installation of lamps without direct manual contact or the necessity of climbing. Concurrently, comprehensive product cost planning and market-driven pricing strategies will be conducted to ensure the device’s affordability and widespread community acceptance. The successful development of this semi-automatic ceiling lamp changer is anticipated to provide a significantly safer, faster, and more convenient alternative for lamp replacement. This remote-operated design is expected to substantially reduce injury incidents associated with current manual methods. By ensuring affordability and market compatibility, this innovation aims to achieve broad community adoption, ultimately contributing to safer environments for lamp maintenance.